The impact of impression management strategies on service quality: Applied research in a sample of oil companies - et. al., Dr. Sarah Ali Saeed Al-Ameri, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to measure the impact of impression management strategies on service quality / applied research in a sample of oil companies, for the purpose of reaching inferences and conclusions that reflect the actual reality of the reflection of the strategies adopted by the Oil Projects Company in the quality of service from the point of view of the oil companies dealing with the company, and to make recommendations in an attempt Contributing to its improvement, since the sample of respondents from oil companies amounted to (293) persons directly related to dealing with the Oil Projects Company. Through e-mail and with the help of company officials and project managers, the statistical analysis program (SPSS V.24) was used.The research reached a number of conclusions, the most important of which is that the Oil Projects Company enjoys 'stimulating an impression and building a good impression', and that was through the respondents working in the oil companies that deal with it and added as a value to the company in front of the oil companies, and the research came out with several recommendations, the most important of which is the necessity of the company's commitment Projects with impression management strategies because of their impact on service quality through the sustainability of impression management strategies by following up on each project with the overall impression management strategies and continuously monitoring the impact of that on service quality.